PERANAN AKUNTAN PUBLIK DAN STANDAR AKUNTANSI KEUANGAN ATAS AKTIVITAS REKSA DANA - Viona Wijaya (Bina Ekonomi, 2007)
Potencies  and characteristics  of Mutual Fund in the  future will be expanded.  Data and statistic about mutual fund  has shown increase  rate. It will always continue with economical  development, and especially  in capital market development. So,  public-accounting's role  for mutual funds activities will increase,  and Financial Accounting Standard which related to mutual  fund will be very  important  to understand.